Strategi Manajemen Pelatihan dan Pengembangan serta Pribadi Tenaga Pendidik dan Kependidikan - Supratman, M Angga; Sujono, Gatot; Usman, Fadly (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
International School Of Taraf International Amanatul Ummah is one of the schools that continues to produce quality students as evidenced by their achievements in both academic and non-academic fields. Therefore, the purpose of this study is to analyze: Strategies, results, and factors supporting and inhibiting training and development management as well as the personality of educators and education personnel. This research is a field research with a qualitative approach, from the informants of the School Coordinator, Educators and Education and Students. The results showed that 1) Management training and development through the following stages: Planning, namely a School Idiom, participatory management, formation of subject teacher deliberations, internal-external training. The implementation process, through needs assessment, provides encouragement and confidence, conditions the learning environment, ensures training implementation, selects training methods, evaluates training programs. The result, through transfers of knowledge, is accomplished. Factors. Supporters; personal teachers, institutions. Blocker; teacher teaching time, teacher vacation time. Meanwhile, 2) personal management of teachers through the following stages: Planning, from the Coordinating School of International Taraf, namely annual meeting discussions, teacher selection materials, creating a culture of partnership, building a climate. As for the teacher through the institutional environment, motivation from outside. The implementation steps, from the coordinator of the International Bertaraf School, namely selecting personal teachers, holding seminars, meeting regulations, building self-confidence, establishing communication, starting from oneself, respecting time, having a social spirit. As for the teacher, namely understanding competence, maintaining dignity, instructive reprimand, students a source of inspiration, wisely admonishing coworkers, giving encouragement help, establishing good relationships with superiors, self-reflection. Factors. Supporters; environment, peer teachers, motivation. Blocker; genetic factors, saturation factors. Result. International Traffic School teachers, Amanatul Ummah, in their competence have been very helpful in terms of learning and as a good role model.